2019
DOI: 10.1155/2019/7190568
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Analysis of Time‐Frequency Features for Vibration Signals of Rolling Bearings Based on Local Frequency

Abstract: The multisource impact signal of rolling bearings often represents nonlinear and nonstationary characteristics, and quantitative description of the complexity of the signal with traditional spectrum analysis methods is difficult to be obtained. In this study, firstly, a novel concept of local frequency is defined to develop the limitation of traditional frequency. Then, an adaptive waveform decomposition method is proposed to extract the time-frequency features of nonstationary signals with multicomponents. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…From equations (2) and 3, h and g are filtered coefficients, p is the number of samples, and u is shifting parameter. e extracted features are used for feature selection viz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From equations (2) and 3, h and g are filtered coefficients, p is the number of samples, and u is shifting parameter. e extracted features are used for feature selection viz.…”
Section: Methodsmentioning
confidence: 99%
“…It emphasizes the importance of both time and frequency domain analysis for nonstationary signals. Tang et al [2] have proposed an adaptive waveform decomposition method of the waveform to extract timefrequency features of nonstationary signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the above methods have achieved good detection results, there are also a small amount of detection errors, so the extraction of a more effective feature that is beneficial to leakage identification needs further study. For non-stationary signals, the Lempel-Ziv index was calculated to characterize the rate of generating new patterns when the signals changed, then measured the complexity of time series (Tang et al, 2019). The results showed that the Lempel-Ziv index can quantitatively measure the complexity of nonlinear signals and effectively distinguish different signals.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of nonstationary signal analysis, according to the different technical means adopted, it can be roughly divided into two categories: nonparametric method and parametric method. In addition, according to the different analysis domain of each method, the above two categories are divided into time-domain methods, frequency domain methods, and time-frequency-domain methods [8][9][10], respectively.…”
Section: Introductionmentioning
confidence: 99%